Performance evaluation of GaN and Si based driver circuits for a SiC MOSFET power switch - Martin J. Carra; Hernan Tacc; Jose Lipovetzky (Institute of Advanced Engineering and Science, 2021)
Silicon Carbide (SiC), new power switches (PSW) require new driver circuits which can take advantage of their new capabilities. In this paper a novel Gallium Nitride (GaN) based gate driver is proposed as a solution to control SiC power switches. The proposed driver is implemented and is performance compared with its silicon (Si) counterparts on a hard switching environment. A thorough evaluation of the energy involved in the switching process is presented showing that the GaN based circuit exhibits similar output losses but reduces the control power needed to operate at a specified frequency.